Pengaruh Ekuitas Merek, Diskon Harga Dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan PT Astra International Daihatsu Di Kota Muara Teweh - Mtw, Arsuni (JURNAL ILMU EKONOMI (MANAJEMEN PERUSAHAAN) DAN BISNIS, 2020)
This study aims to analyze the effect of brand equity, price discounts and customer satisfaction oncustomer loyalty of PT. Astra international Daihatsu in the city of Muara Teweh. The research methodused was a questionnaire distributed to the population in this study were the customers of PT. AstraInternational - Daihatsu who lives in Muara Teweh City and the number is unknown. The sample usedin this study is Consumer respondents who have already purchased Daihatsu products and Consumerswho live in the Muara Teweh area. The measurement uses a Likert scale with a weighting scale of 1 to5. The results show that there is an influence of brand equity (X1) on customer loyalty (Y), so thatincreasing brand awareness increases customer loyalty. Thus to increase customer loyalty at PT. AstraInternational - Daihatsu can be done by increasing brand equity. There is an influence of pricediscount (X2) on customer loyalty (Y), so the more discounted prices the more customer loyaltyincreases. Thus to increase customer loyalty at PT. Astra International - Daihatsu can be done byincreasing price discounts. There is an influence of customer satisfaction (X3) on customer loyalty(Y), so the more customer satisfaction increases the more customer loyalty increases. Thus to increasecustomer loyalty at PT. Astra International - Daihatsu can be done by increasing customer satisfaction